Nonlinear Internal Control System in Business - M. A. Zholayeva; K. Z. Saduakasov; Z. U. Urazbayeva; M. A. Serikova (Экономика: стратегия и практика, 2024)
The purpose of the written study is to study the relationship between the qualifications of the CFO and the nonlinear system of the firm’s internal control system. We used three indicators of the competence of the CFO: financial education, accounting, seniority, and education. Using the model of Kazakhstan companies registered on the stock exchange in 2023. In the methodology of the internal control system, in which stimuli cause a reverse response, the internal control system should be recognized as a nonlinear approach that can have a high impact if it has little impact. The results of this study show a negative relationship between the financial, accounting experience of a CFO and work experience under a nonlinear system of internal control, which indicates that firms with high-quality CFO are facing a nonlinear internal control system in business. A business management team with a large number of employees is associated with an effective internal control system. In addition, the political preferences of senior management directly and indirectly affect the quality of financial statements through the internal control system. Several reliability tests confirm our main results. The results show that a capable CFO can effectively implement a suitable subsystem. The results of the study of a nonlinear system of internal control in business, in terms of improving individual elements of internal control in companies, can be used by members of audit firms.